UJI AKTIVITAS EKSTRAK ETANOL DAUN TAPAK DARA (Catharanthus roseus L.) SEBAGAI ANTIBAKTERI Streptococcus mutans - Triastinurmiatiningsih, .; Komala, Oom; Salsabila, Nadia Muna (Universitas Pakuan, 2023)
Dental caries is a localized dental disease that damages the hard tissues of the teeth formed from the accumulation of plaque on the tooth surface. Tapak dara leaf (Catharanthus roseus L.) is known to have antibacterial activity derived from secondary metabolites, namely Triterpenoid Indole Alkaloid (TIA), flavonoids, saponins, steroids, and tannins. The purpose of the study was to analyze the activity of 96% ethanol extract of tapak dara leaves with the highest inhibitory power against Streptococcus mutans bacteria and determine chemical compounds through phytochemical tests. Antibacterial testing of 96% ethanol extract of virgin tread leaves using disc diffusion method with LDH (Width Inhibitory Power) measurement. Antibacterial tests of ethanol extract of tapak dara leaf were carried out on concentrations of 60%, 65%, 70%, and 75%. DMSO solvent 10% as a negative control and amoxicillin antibiotic 500 ppm as a positive control. The results showed that antibacterial test results at a concentration of 75% showed antibacterial activity with the highest inhibitory power averaging 6.27 mm. Phytochemical test results show that 96% ethanol extract of tapak dara leaf contains alkaloids, flavonoids, tannins, saponins, and steroids